2020
DOI: 10.2174/1389200221666200103090757
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Pharmacokinetics of Phytochemicals in the Human Body

Abstract: Background: Phytochemicals are obtained from various plants and used for the treatment of diseases as both traditional and modern medicines. Poor bioavailability of phytochemicals is a major concern in applying phytochemicals as a therapeutic agent. It is, therefore, necessary to understand the metabolism and pharmacokinetics of phytochemicals for its implication as a therapeutic agent. Methods: Articles on the metabolism of phytochemicals from the PubMed database. The articles were classified into the diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 228 publications
0
17
0
Order By: Relevance
“…Several clinical trials using phytochemicals have been conducted for various diseases or immune-related activity, but there are currently no clinical trials for phytochemicals with ICI monotherapy or combination agents with other immunomodulatory anti-cancer agents. This may be due to the poor pharmacokinetics and pharmacodynamics features of a large number of phytochemicals [261]. Current ICI therapy is used alone or combined with conventional chemotherapy in patients with certain cancer types, while severe side effects can be accompanied during combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials using phytochemicals have been conducted for various diseases or immune-related activity, but there are currently no clinical trials for phytochemicals with ICI monotherapy or combination agents with other immunomodulatory anti-cancer agents. This may be due to the poor pharmacokinetics and pharmacodynamics features of a large number of phytochemicals [261]. Current ICI therapy is used alone or combined with conventional chemotherapy in patients with certain cancer types, while severe side effects can be accompanied during combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of phytochemicals depends on the individual’s digestive ability, membrane transporters, metabolizing enzymes and gut microbiota. The exogenous compounds (phytochemicals) are metabolize in gut microbiota, and phase I and phase II metabolism through oxidation, hydration, demethylation, hydrogenation, and SH 2 addition, as well as different glucuronide/sulfate conjugates [ 32 ]. A recent study reported that the structurally similar compounds to MBC are orally bioavailable and undergo gut microbiotic metabolism (dehydroxylation and reduction), and phase II metabolism (glucuronidation and sulfation) in healthy humans [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood collection times of 0.0, 0.5, 1, 2, 4, 6, 8, 12, 24, and 48 h are fairly common, although these can be modified for subject convenience. To be as efficient and practical as possible, a single dose of extract is administered in the morning (with or without food) and blood sampling will span at least 12 h the first day, with subsequent blood draws at 24 and perhaps 48 h. Given that most phytochemicals have fairly short elimination half-lives in humans, samples obtained after 24 h may not be necessary ( 30 , 32 ). A clearly defined biomarker as determined by pre-clinical studies is essential for the clinical PK study.…”
Section: The Clinical Study: the Nitty-gritty Detailsmentioning
confidence: 99%